Interactive Online Storytelling Using AR Technology for the Familia Kreativa Community - Yanuar Rahman; Dyah Ayu Wiwid Sintowoko; Ananda Risya Triani (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
Community service initiatives involving interactive online storytelling using Augmented Reality (AR) technology aim to provide a novel educational experience for children aged 6 to 9, particularly members of the Familia Kreativa community. Storytelling is a powerful tool for imparting moral values, fostering creativity, and promoting reading habits among children. However, contemporary delivery methods are necessary to meet the needs of today's generation. AR technology was selected for its capacity to deliver interactive and immersive three-dimensional visual elements, which enhance participant engagement. This program comprised four phases: preparation, development of storytelling materials and modules, implementation of two online storytelling sessions, and evaluation. During the sessions, participants used smart devices to scan worksheets, which revealed AR features and objects. This activity involved direct interaction between participants and the storyteller through questions, answers, and visual exploration. The results indicate that AR technology improves participants' focus, interaction, and comprehension of the narratives. Children demonstrated better recall of story elements, while parents noted that this approach effectively reduced boredom and enhanced the learning experience. AR technology shows substantial potential for fostering creative learning and visual literacy in early childhood. Its use in this initiative aligns with the goals of quality education under SDG 4 and creates opportunities for technical innovation in the broader context of early childhood education development.